Diagnostic Analyses of Retinal Dystrophy Genes: Current Status and Perspective - Bolz, Hanno Jörn (Klinische Monatsblätter für Augenheilkunde, 2021)
Over the past decade, novel high-throughput DNA sequencing technologies have revolutionised both research and diagnostic testing for monogenic disorders. This applies particularly to genetically very heterogeneous disorders like retinal dystrophies (RDs). Next-generation sequencing (NGS) today is considered as reliable as Sanger sequencing, which had been the gold standard for decades. Today, comprehensive NGS-based diagnostic testing reveals the causative mutations in the majority of RD patients, with important implications for genetic counselling for recurrence risks and personalised medical management (from interdisciplinary surveillance to prophylactic measures and, albeit yet rare, [gene] therapy). While DNA sequencing is – in most cases – no longer the diagnostic bottleneck, one needs to be aware of interpretation pitfalls and dead ends. The advent of new (NGS) technologies will solve some of these issues. However, specialised medical geneticists who are familiar with the peculiarities of certain RD genes and closely interact with ophthalmologists will remain key to successful RD research and diagnostic testing for the benefit of the patients. This review sheds light on the current state of the field, its challenges and potential solutions.
Keywords: next-generation sequencing; retinal dystrophy; genetics